2015
DOI: 10.1177/0046958015571131
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statins by Medicare Beneficiaries Post Myocardial Infarction

Abstract: Even though guidelines strongly recommend that patients receive a statin for secondary prevention after an acute myocardial infarction (MI), many elderly patients do not fill a statin prescription within 30 days of discharge. This paper assesses whether patterns of statin use by Medicare beneficiaries post-discharge may be due to a mix of high-quality and low-quality physicians. Our data come from the Centers for Medicare & Medicaid Services (CMS) Chronic Condition Data Warehouse (CCW) and include 100% of Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Prescribing among patients cared for by specialist providers (eg, cardiologists) may have seen changes in prescribing patterns. Patients do not always fill their prescriptions for statin therapy 19 or other classes of medications, such as antihypertensives. 20 Assessment of statin therapy was made according to prescribing pattern not prescriptions fills, as this was beyond the scope of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing among patients cared for by specialist providers (eg, cardiologists) may have seen changes in prescribing patterns. Patients do not always fill their prescriptions for statin therapy 19 or other classes of medications, such as antihypertensives. 20 Assessment of statin therapy was made according to prescribing pattern not prescriptions fills, as this was beyond the scope of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the observed treatment rates in each hospital referral region were calculated as the proportion of patients in the hospital referral region categorized as receiving surgery, physical therapy, and watchful waiting. Risk-adjusted treatment rates for each hospital referral region were then calculated as the average predicted probability of treatment, estimated with regression models as previously described, across patients in the hospital referral region 40 , 53 - 55 . The area treatment rate differential for each hospital referral region was finally calculated by subtracting the observed rate from the expected rate for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The results from other work also suggest patient-centered treatment decisions and the use of practice-based evidence. In two previous papers, 62% of patients surviving an AMI had a statin available within 30 days of discharge, far below what was recommended by clinical guidelines [ 91 , 106 ]. In these studies, lower statin-use rates were observed for patients with complex comorbidities and a history of adverse events known to be correlated with statin use in population-based studies [ 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%